Two numerical models of the solidification structure of massive ductile cast-iron casting - Stransky, Karel (Materiali in tehnologije, 2010)
An original three-dimensional (3D) model of solidification is used to describe the process of solidification and cooling of massive (500 * 1000 * 500) mm cast-iron sand moulds castings. The calculated mode of the kinetics of the temperature field of the casting was verified during casting with temperature measurements in selected points. The sizes and positions (xsubi, ysubi, zsubi, where i = 1, 2, 3 is the number of samples taken) of the experimental samples are exactly defined and corresponding with the decreasing rate of solidification. The experimental samples - 15 mm in diameter and 12 mm high - were metallographically analysed and also in terms of heterogeneity of chemical composition. The coordinates xsubi, ysubi, zsubi characterise approximately - within an accuracy of 5 mm - the centres of the samples. Successively, the local solidification time Q (i.e. the time the specified position of the casting, defined by the coordinates xsubi, ysubi, zsubi, remained within the temperature range between the liquid and solid curves) is also calculated using the 3 D model. The following dependences are later determined according to experimental and calculated data: the average size of graphite spheroids rsubg and of graphite cells Rsubb as well as the average distances among the particles of graphite Lsubg - always as function of the local solidification time Q xsubi, ysubi, zsubi. Furthermore, it was founded that the given characteristics of the structure of the cast iron rsubg, Rsubb and Lsubg are directly proportional to the logarithm of the local solidification time. The original spatial model of solidification can therefore be used therefore as first approximation for the ironparts. This paper creates the starting point for the estimation of the assessment of the casting structure of massive cast iron parts. This paper creates the starting point for the estimation of the local mechanical properties and fracture behaviour of massive ductile cast iron castings.
Keywords: siva litina; strjevanje; mikrostruktura; kroglasti grafit